PERCEPTIONS OF FIRST-YEAR PRECLINICAL MEDICAL STUDENTS ON THE RELATIONSHIP BETWEEN INTERACTIVE LECTURE TEACHING METHODS AND THE DEVELOPMENT OF GENERIC SKILLS AS WELL AS INFLUENCING FACTORS - Kane, Nathan; Anastasia, Gisella; Soesilo, Daniel Ardian; Puspadewi, Natalia (Universitas Gadjah Mada, 2025)
Background: Generic skills, such as critical thinking, communication, teamwork, and social judgment, are essential elements in modern medical education. Interactive lectures in large classes, which combine material delivery with discussion and feedback, have become one of the effective approaches. However, the implementation of these methods in large classes faces various challenges, such as uneven student participation and a lack of confidence among students. Aims: This study aims to explore first-year pre-clinical medical students' perceptions of the relationship between interactive lectures in large classes and the development of generic skills, as well as the factors that influence this process. Methods: This study employs a qualitative phenomenological design with in-depth interviews involving eight first-year pre-clinical students at the Faculty of Medicine, Atma Jaya Catholic University of Indonesia. Data were analysed using a thematic approach to explore key themes related to the development of generic skills. Results: The results show that interactive lecture in large classes, teacher quality plays a significant role in facilitating discussions and providing feedback. Class activities, such as group discussions and feedback sessions, significantly contribute to the development of generic skills. Students' motivation and self-confidence, along with supportive group members, further enhance these skills. Additionally, the large number of students in the class is seen as a valuable platform for practicing communication skills and building confidence. However, a notable obstacle is the initial session where lecturers rely on slides with excessive text, which reduces students' interest and engagement. Conclusions: Interactive lectures in large classes are effective in supporting the development of students' generic skills through discussion, presentation, and feedback. Its success is influenced by teacher quality, the learning environment, and student motivation. Improving the quality of lecturer presentations is necessary to enhance the effectiveness of this method.